UPAYA PEMERINTAH DALAM PENATAAN PEMBANGUNAN RUMAH TOKO (RUKO) DI KOTA PEKANBARU (STUDI KASUS PEMBANGUNAN KAWASAN RUMAH TOKO (RUKO) DI KECAMATAN TAMPAN TAHUN 2010-2013) - Kamal "; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine the efforts made by the Government of Pekanbaru in structuring the development of the home store (shop) in the city of Pekanbaru, especially in Sub Handsome. The background of this study is the proliferation of commercial buildings and as if ignoring the environmental creed particular catchment areas and green open spaces.This study used a qualitative approach in obtaining and analyzing data, for data analysis, a policy, the theory of coordination and control theory. The informant withdrawal technique performed with a purposive approach to the informant, the data in this study was obtained through interviews and observation techniques and study documentation. Descriptive data were analyzed during the study.The results of this study prove that there has been no real effort of the government in structuring the development of home stores, especially in Sub Handsome Pekanbaru. Coordination of activities undertaken by the government was limited to ensure completeness of the administrative requirements in order to obtain building permits. Supervision is done well only to observe the implementation of the technical development is in accordance with the rules of minimum distance and the construction of infiltration wells. Even then considered not maximal activity. Moreover, the absence of specific rules regarding the use of space to cause irregularities housing construction, especially in Sub Handsome store Pekanbaru.Keywords: Policy, Licensing Home Store, Coordination and Supervision